2011
DOI: 10.2174/138920311796957603
|View full text |Cite
|
Sign up to set email alerts
|

Solvent and Lipid Accessibility Prediction as a Basis for Model Quality Assessment in Soluble and Membrane Proteins

Abstract: On-going efforts to improve protein structure prediction stimulate the development of scoring functions and methods for model quality assessment (MQA) that can be used to rank and select the best protein models for further refinement. In this work, sequence-based prediction of relative solvent accessibility (RSA) is employed as a basis for a simple MQA method for soluble proteins, and subsequently extended to the much less explored case of (alpha-helical) membrane proteins. In analogy to soluble proteins, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
(109 reference statements)
0
8
0
1
Order By: Relevance
“…The average ASA of 20 amino acids in TMPs are significantly different from that of soluble proteins, even in non-TM segments [65]; hence, ASA predictors of soluble proteins are not applicable to TMPs. However, some studies on predicting ASA specifically for TMPs [65][67] have been developed, which showed significantly improved accuracy of ASA prediction in TM segments. We used one of these methods MPRAP [67] to predict ASA for both targets and templates, which separates different segments of TMP and predicts the entire TMP sequence without using its topology structures as input.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average ASA of 20 amino acids in TMPs are significantly different from that of soluble proteins, even in non-TM segments [65]; hence, ASA predictors of soluble proteins are not applicable to TMPs. However, some studies on predicting ASA specifically for TMPs [65][67] have been developed, which showed significantly improved accuracy of ASA prediction in TM segments. We used one of these methods MPRAP [67] to predict ASA for both targets and templates, which separates different segments of TMP and predicts the entire TMP sequence without using its topology structures as input.…”
Section: Methodsmentioning
confidence: 99%
“…However, some studies on predicting ASA specifically for TMPs [65][67] have been developed, which showed significantly improved accuracy of ASA prediction in TM segments. We used one of these methods MPRAP [67] to predict ASA for both targets and templates, which separates different segments of TMP and predicts the entire TMP sequence without using its topology structures as input. To reduce the impact of prediction errors in the alignment, both the target and template used predicted ASA to construct profiles.…”
Section: Methodsmentioning
confidence: 99%
“…By adding MP-specific features such as lipid accessibility (Phatak et al, 2011) and topology structure (Tsirigos et al, 2015) to our deep learning models, we can improve contact accuracy by about 1%. This might be because our deep learning models have already implicitly learned them.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, accessible surface area (ASA) is much different for OMPs to be predicted. We used a recent published method MPRAP (Phatak et al, 2011) to generate the ASA for all the residues in each sequence in our dataset. The predicted ASA were directly used in contact prediction as an element in the input feature vector.…”
Section: Lipid Layer Accessibility Featurementioning
confidence: 99%